Current status of coenurosis in Uzbekistan - Ravshanov Mirjalol; Narziyev Bakhtiyor; Djumanov Sobir; Narziyeva Nargiza; Mukhtarov Bakhtyar (BIO Web of Conferences)
This study is dedicated to examining the prevalence and causes of coenurosis in sheep across various regions of Uzbekistan, with a particular focus on the Jizzakh, Navoi, and Samarkand provinces. The investigation found that coenurosis was identified in 156 out of 6,750 sheep (2.3%), with the highest incidence observed in the Nurabad district (10.3%) and the lowest in the Konimekh district (1.5%). The disease predominantly affected sheep between 9 and 14 months of age. The primary source of infection was the ingestion of feed contaminated with parasite eggs, which was often linked to improper disposal of infected animal remains and the presence of stray dogs. Pathological examinations confirmed the presence of cysts in the brains of affected sheep, causing neurological symptoms such as loss of coordination, visual impairments, and behavioral changes. The study highlights the importance of adhering to veterinary regulations, conducting regular deworming of dogs, and increasing awareness among livestock farmers to prevent the spread of coenurosis. The application of modern diagnostic techniques such as MRI and ultrasound aids in the early detection and treatment of the disease, thereby reducing economic losses and promoting more effective health management of agricultural animals, including cattle.